Chromosome-level genome assembly, reannotation and decoding of a Trichomonas vaginalis clinical isolate from Shiyan, Central China - Yanqing Zhao; Yinjie Lian; Wei Guan; Peng Wu; Shuguo Yang; Jian Li (Decoding Infection and Transmission)
Introduction: Trichomonas vaginalis trophozoite is a pathogen that causes trichomoniasis, the most common neglected sexually transmitted disease. The reference genome of T. vaginalis is derived from the G3 strain. Although many strains are widely present in China, no genomic information is available for relevant studies. Methods: Clinical T. vaginalis isolates were collected, cultured and sequenced via the next-generation Illumina, SMRT DNA sequencing platform and chromosome conformation capture (Hi-C) technologies. Results: The present assembled TV-THS1 genome, spanning 185.45 Mb, was comprised of 934 contigs with a contig N50 length of 467.79 kb anchored to six pseudochromosomes, accounting for more than 88 % of the assembled genome (164.56 Mb). The genome included 24,691 protein-coding genes, 24,376 of which (98.72 %) were functionally interpreted. A total of 131.74 Mb (71.03 %) of the assembled sequences were identified as repetitive sequences, and 5302 corresponding genes were annotated in Maverick elements. Compared with the published T. vaginalis G3 reference genome, substantial differences have been revealed. Comparative genome analysis revealed that genes related to expansion during evolution mainly participated in cell adhesion and the biosynthesis of specialized metabolites, such as those involved in binding and catalytic activity. Conclusions: A chromosome-level reference T. vaginalis TV-THS1 genome was obtained, providing comprehensive insight into T. vaginalis evolution and the molecular mechanisms of T. vaginalis pathogenicity. This work offers valuable data for pathogen-host interaction analysis, clinical diagnosis, treatment and prevention of trichomoniasis.